Minaccia dellautostima e fantasie grandiose nel narcisismo non patologico - Guido Veronese; Giovanni Maria Ruggiero; Sandra Sassaroli; Marco Castiglioni (Research in Psychotherapy, 2010)
The study explored the qualitative features of: a) memories of threat to self-esteem, b) grandiose fantasies and c) relaxing scenarios, experimentally induced in a non-clinical participant sample. A group of 103 young university students produced and transcribed personal memories of threat to self-esteem, grandiose fantasies and relaxing scenes. A five point scale was designed ad hoc to enable three independent raters to assess the biological, psychological and relational contents of each of the texts. Inter-rater agreement was satisfactory. Memories of threat to self-esteem and grandiose fantasies were mainly socio- relational, while relaxing scenarios were characterised by both relational and biological elements. With reference to the biological dimension, there was also significant correlation between memories of threat to self-esteem and grandiose fantasies.